Analysis of Intrinsic Motivation and Efficiency of Administrative Procedures for Promotion of Functional Lecturers from Lecturer to Senior Lecturer at the State Christian Institute of Kupang - LINO, Ellen Devis; KASE, Petrus; Kerihi, Anthon (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study will discuss the factors that influence the intrinsic motivation of lecturers in the process of functional promotion from Lecturer to Associate Lecturer in the State Christian Religious College (PTKKN) under the auspices of the Ministry of Religious Affairs of the Republic of Indonesia, namely the State Christian Institute (IAKN) Kupang. In addition, this study will also analyze the efficiency of the administrative procedures applied in the process, including the obstacles faced and efforts to improve them. The method used is a qualitative research method with a case study research type. The findings and analysis of the intrinsic motivation of lecturers at IAKN Kupang in applying for functional promotion from Lecturer to Associate Lecturer are driven by the need to achieve recognition and self-actualization as described in Maslow's theory. The lecturers' desire to develop academically, gain recognition for scientific performance, and contribute more broadly to the tridharma are the main driving forces. However, this motivation cannot always be implemented optimally due to obstacles in the efficiency of administrative procedures. Irregular flow, minimal mentoring, and lack of clarity of technical information lead to feelings of insecurity, confusion, and psychological exhaustion, which directly reduce the lecturers' intrinsic motivation. Low administrative efficiency not only impacts individual productivity but also has implications for the overall development of the institution. Therefore, the success of the lecturer promotion process is inextricably linked to the integration of the lecturer's intrinsic motivation and an efficient and supportive institutional administration system.